Listeria monocytogenes: a promising vector for tumor immunotherapy - Ding, Yi-Dan; Shu, Lin-Zhen; He, Rui-Shan; Chen, Kai-Yun; Deng, Yan-Juan; Zhou, Zhi-Bin; Xiong, Ying; Deng, Huan (Frontiers in Immunology, 2023)
Cancer receives enduring international attention due to its extremely high morbidity and mortality.Immunotherapy, which is generally expected to overcome the limits of traditional treatments, serves as a promising direction for patients with recurrent or metastatic malignancies. Bacteria-based vectors such as Listeria monocytogenes take advantage of their unique characteristics, including preferential infection of host antigen presenting cells, intracellular growth within immune cells, and intercellular dissemination, to further improve the efficacy and minimize off-target effects of tailed immune treatments. Listeria monocytogenes can reshape the tumor microenvironment to bolster the anti-tumor effects both through the enhancement of T cells activity and a decrease in the frequency and population of immunosuppressive cells. Modified Listeria monocytogenes has been employed as a tool to elicit immune responses against different tumor cells. Currently, Listeria monocytogenes vaccine alone is insufficient to treat all patients effectively, which can be addressed if combined with other treatments, such as immune checkpoint inhibitors, reactivated adoptive cell therapy, and 2 radiotherapy. This review summarizes the recent advances in the molecular mechanisms underlying the involvement of Listeria monocytogenes vaccine in anti-tumor immunity, and discusses the most concerned issues for future research.